Salvage Therapy with Sofosbuvir/Velpatasvir/Voxilaprevir in DAA-experienced Patients: Results from a Prospective Canadian Registry. (2nd March 2021) - Onofrio, Fernanda Q; Cooper, Curtis; Borgia, Sergio M; Vachon, Marie-Louise; Ramji, Alnoor; Lilly, Leslie B; Wong, Alexander; Booth, Joshua; Sattar, Izza; Morales, Heidy; Lee, Samuel; Conway, Brian; et al.
Abstract: Background: Despite the current highly effective therapies with direct-acting antiviral agents (DAAs), some patients with chronic hepatitis C virus (HCV) infection still do not achieve sustained virological response (SVR) and require retreatment. Sofosbuvir/velpatasvir/voxilaprevir (SVV) is recommended as the first-line retreatment option for most patients. The aim of this study was to evaluate the efficacy of SVV as salvage therapy after at least one course of DAA. Methods: Data were collected on all HCV-infected patients who failed DAAs and were prescribed SVV from a prospective Canadian registry (CANUHC) including 17 sites across Canada. Factors associated with failure to achieve SVR with SVV therapy and the utility of RAS testing and ribavirin use were evaluated. Results: A total of 128 patients received SVV after non-SVR with DAA treatment: 80% male, median age 57.5 (31–86), 44% cirrhotic, and 17 patients post liver transplant. First line regimens included: sofosbuvir/velpatasvir (27.3%), sofosbuvir/ledipasvir (26.5%), grazoprevir/elbasvir (12.5%), other (33.5%). Ribavirin was added to SVV in 26 patients due to past sofosbuvir/velpatasvir use (n = 8), complex resistance associated substitution profiles (n = 16) and/or cirrhosis (n = 9). Overall SVR rate was 96% (123/128). Of 35 patients who previously failed sofosbuvir/velpatasvir, 31 (88.5%) achieved SVR compared to 92 of 93 (99%) among those receiving any other regimen ( P  = .01). Conclusions: Similar to reports from phase 3 clinical trials, SVV proved highly effective as salvage therapy for patients who failed a previous DAA therapy. Those who failed SVV had at least 2 of the following factors: genotype 3, presence of cirrhosis, past liver transplantation, past exposure to sofosbuvir/velpatasvir and/or complex resistance profiles. Abstract : Sofosbuvir/velpatasvir/voxilaprevir was highly effective (96% sustained virologic response) after direct-acting antiviral failure. The combination of at least 2 of the following: genotype 3, cirrhosis, prior liver transplantation, past sofosbuvir/velpatasvir treatment, and complex resistance profiles were more common among nonresponders to this regimen.